(untitled) (Pedagogical Horizons, 2021)
Due to the enormous development of Internet-based technology, there is a growing interest in integrating it into educational processes as part of the learning environment in the classroom. There are many studies on information systems about the behavior of students, but there are still few studies in the German speaking countries. In this paper, the ADDIE design model for the comprehensible planning of the self-created media product is presented and the Technology Acceptance Model (TAM) is analyzed in order to investigate the behavioral intention of the students when using the digital media product. A questionnaire, which had already been used several times in other studies, was translated into German and modified using existing scales from previous TAM instruments. Twenty-two students filled out the questionnaire, providing answers on Perceived Utility (PU), Perceived User Friendliness (PEU), Attitude to Use (A), and Behavioral Intention to Use (BIU) of the digital media product. At the end of the empirical work an interpretation of the evaluation results will take place.